(untitled) (Hekima Review, 2001)
AS AFRICAN PRIESTS AND RELIGIOUS, the community here at Hekima College continues to labour under the banner of Christ. Hekima Review therefore continues to reflect our wholehearted engagement in critical theological reflections on the problems that plague our continent from within and without. Through this apostolic labour, fresh waters have recently passed under the bridge of theology here. The articles in this issue of Hekima Review are freshening waters from beneath this bridge of theology